2009
DOI: 10.1111/j.1460-9568.2009.06808.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel type of interplexiform amacrine cell in the mouse retina

Abstract: Mammalian retinas comprise an enormous variety of amacrine cells with distinct properties and functions. The present paper describes a new interplexiform amacrine cell type in the mouse retina. A transgenic mouse mutant was used that expressed the gene for the enhanced green fluorescent protein (EGFP) instead of the coding DNA of connexin45 in several retinal cell classes, among which a single amacrine cell population was most prominently labelled. Staining for EGFP and different marker proteins showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 69 publications
0
31
0
Order By: Relevance
“…For example, in the wild-type mouse retina, ionotropic GABA receptors are expressed on HCs (Feigenspan and Weiler, 2004) acting as auto-receptors (Liu et al, 2013) but are not expressed on cones (Kemmler et al, 2014), whereas rd1 cones do express GABA A/C receptors (Pattnaik et al, 2000). Notably, also GABAergic interplexiform cells form synapses in the outer retina (Dedek et al, 2009) and therefore may participate in controlling the activity of neurons in the outer rd1 retina.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in the wild-type mouse retina, ionotropic GABA receptors are expressed on HCs (Feigenspan and Weiler, 2004) acting as auto-receptors (Liu et al, 2013) but are not expressed on cones (Kemmler et al, 2014), whereas rd1 cones do express GABA A/C receptors (Pattnaik et al, 2000). Notably, also GABAergic interplexiform cells form synapses in the outer retina (Dedek et al, 2009) and therefore may participate in controlling the activity of neurons in the outer rd1 retina.…”
Section: Resultsmentioning
confidence: 99%
“…In mammalian retina some of the GABAergic neurons in the inner nuclear layer are GABAergic interplexiform cells ( rodent : [32, 4649]; cat : [17, 25, 32, 46, 50]; rabbit : [32, 51]; primate : [28, 52, 53]; human : [32, 54, 55]) (Figure 1). Although most of them contain a second neurotransmitter (dopamine, acetylcholine, NO) as well as GABA, types of interplexiform cell containing only GABA have also been described [49, 53].…”
Section: Gabaergic Neurons In Retinamentioning
confidence: 99%
“…Immunohistochemistry was performed as described previously (Dedek et al, 2009). Briefly, the posterior eyecup was fixed for 15-30 min in 2-4% paraformaldehyde in 0.1 M phosphate buffer (PB, pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…Medium-field and wide-field amacrine (WFA) cells exhibit large dendritic arbors (up to 1 mm). These cells are GABAergic and comprise ϳ20 subtypes (Badea and Nathans, 2004;Lin and Masland, 2006;Pérez De Sevilla Müller et al, 2007;Dedek et al, 2009;Majumdar et al, 2009). WFA cells either mediate lateral interactions, which are often confined to a single stratum in the IPL (Hsueh et al, 2008), or provide local reciprocal inhibition, as was recently shown for A17 cells (Grimes et al, 2010).…”
Section: Introductionmentioning
confidence: 99%